Understanding High Achievement: The Case for Eminence - Baker, Joseph; Schorer, Jörg; Lemez, Srdjan; Wattie, Nick (Frontiers in Psychology, 2019)
The development of the field of sport expertise over the past 20 years has been remarkable and our understanding of the varying factors affecting athlete development and motor skill acquisition has expanded considerably. Recently, there has been a push towards more sophisticated research designs to continue the advancement of our understanding of sport expertise. Even in a population of performers at the highest levels of performance and competition (e.g., participants in professional sports or those who compete at Olympic Games), there are those with obvious superiority compared to others in the cohort, such as those who win ‘most valuable player’ awards or who are elected to the Hall of Fame. This paper builds a case that athletes who reach this level of achievement possess a more advanced level of skill than those at the elite or expert stage and we refer to this stage of development as ‘eminence’. This paper explores the notion of eminence and provides converging forms of evidence for the division between expertise and eminence. Moreover, it explores the implications of this division for the further examination of skill acquisition across the lifespan.